The Relationship between the Duration of Suffering from Diabetes and HbA1c Levels with the Degree of Liver Stiffness in Type 2 Diabetes Mellitus Patients - Faza Khilwan Amna; Maya Nuriya Widyasari; Hery Djagat Purnomo; Frederica Mardiana Wahyuni; Bambang Satoto; Hermina Sukmaningtyas (RSUP Dr. Kariadi, 2024)
BACKGROUND : Type 2 diabetes mellitus (DM) is one of the major problems faced by the health system. Diabetes is a multifactorial, chronic and progressive metabolic disorder characterized by chronic hyperglycemia. Persistent hyperglycemia is associated with long-term damage to the liver. Ultrasound elastography is one of imaging modality that can assess liver stiffness, thus can assist clinicians in determining therapy, evaluating, and predicting disease progression. AIMS : Aim of this study was to determine the relationship between liver stiffness degree by using ultrasound elastography with the duration of T2DM and HbA1c levels. METHOD : This study was an observational analytic research with a cross-sectional approach which carried out from May to September 2022 at the radiology department of Dr. Kariadi Hospital Semarang. Fifty subjects were included in this study and Rank-Spearman correlation test was used to analyze the relationship between liver stiffness degree with T2DM duration and HbA1c levels. RESULT : Using ultrasonography elastography, the liver stiffness average was 7.92 + 6.72 kPa. The average of HbA1c levels was 8.55 + 2.63%. T2DM duration average was 9.10 + 6.50 years. The rank-spearman test showed a significant correlation between HbA1c levels and the degree of liver stiffness (p = 0.000) with a correlation coefficient (r) of 0.68. There was no significant correlation between the T2DM duration and the degree of liver stiffness (p = 0.052). CONCLUSION : There was a significant correlation between liver stiffness and HbA1c levels, but there is no correlation between liver stiffness and T2DM duration